“SECURITY SENSITIVE AREA” AS A REASON FOR RESTRICTING FREEDOM OF ASSEMBLY - Stevandić, Danilo (Political Review, 2025)
A security-sensitive area represents a defined area around buildings of the highest authorities, buildings of special importance for the security of the state, and certain institutions whose basic purpose is to provide undisturbed work of the state bodies by applying a specific regime of public assembly in the area. After the introductory exposure, the issue of assembly location has been processed from the jurisprudential point of view, after which a legal history and a comparative law analysis of protected areas as a way of restricting assembly were performed. In the fourth part, restrictions on assembly locations in the Republic of Serbia were analysed by applying the legal dogmatics method. The author concludes that applying a specific legal regime of assembly in a protected area has constitutional justification, but only if such a regime implies a relative ban on assembly, along with applying the proportionality principle. Under the constitutional law, a protected area cannot represent a justifiable reason for restricting freedom of assembly per se, but it has to be directly related to some of the international law or the constitutional law grounds for restricting freedom of assembly. Law on Public Assembly in the Republic of Serbia prescribes restrictions on assembly locations, including locations which, according to the comparative law experiences, may be considered a protected area, but the constitutionality of some of the restrictions may be questioned for valid reasons since they are defined in advance by the law, and they are also general and absolute.